Magic season : a son's story - Rouse, Wade (Hanover Square Press, 2022)
Before his success in public relations, his loving marriage and his storied writing career, Wade Rouse was simply Ted Rouse's son. A queer kid in a conservative Ozarks community, Wade struggled at a young age to garner his father's approval and find his voice. For his part, Ted was a hard-lined engineer, offering little emotional support or encouragement. But Wade and Ted had one thing in common: an undying love of the St. Louis Cardinals. For decades, baseball offered Wade and his father a shared vocabulary, a way to stay in touch, to connect and to express their emotions. But when his father's health takes a turn for the worst, Wade returns to southwest Missouri to share one final season with his father. As the Cards race towards a dramatic pennant race, Wade and his father begin to open up in way they never thought possible. Together, inning by inning during their own magic season, they'll move towards forgiveness, reconciliation, and peace.